Conformational and vibrational study of cis-diamminedichloropalladium(ii) - Fiuza, Sónia M. (2010)
A conformational and vibrational analysis of cis-diamminedichloropalladium(ii) (cDDPd) is reported. Several theoretical methods (from Hartree-Fock to Møller-Plesset and Density Functional Theory) combined with different all-electron basis-sets are evaluated, in view of determining the best suited strategy for accurately representing this molecule. This choice is based on the best compromise between accuracy and computational requirements. Different scaling models were tested for obtaining the best scaling schemes of the vibrational modes to be used in this type of inorganic systems. The structural parameters and vibrational results predicted by the calculations are compared with the corresponding experimental data, namely X-ray structure and vibrational spectra. Finally, a complete assignment of the cDDPd vibrational spectra is presented.